Assessment of neuronal autoantibodies in patients with small cell lung cancer treated with chemotherapy with or without ipilimumab. (1st February 2018) - Hardy-Werbin, M.; Arpí, O.; Taus, A.; Rocha, P.; Joseph-Pietras, D.; Nolan, L.; Danson, S.; Griffiths, R.; Lopez-Botet, M.; Rovira, A.; Albanell, J.; Ottensmeier, C. H.; et al.
ABSTRACT: Small-cell lung cancer (SCLC) is often associated with paraneoplastic syndromes. To assess the role of anti-neuronal autoantibodies (NAAs) as biomarkers of treatment outcome, we assessed NAAs in serial samples from SCLC patients treated with chemoimmunotherapy compared to chemotherapy alone. We evaluated 2 cohorts: in cohort 1 (C1), 47 patients received standard platinum/etoposide, and in cohort 2 (C2), 38 patients received ipilimumab, carboplatin and etoposide. Serum samples at baseline and subsequent time points were analyzed for the presence of NAAs. NAAs were detected at baseline in 25 patients (53.2%) in C1 and in 20 patients (52.6%) in C2 (most frequently anti-Sox1). NAA at baseline was associated with limited disease (75% vs 50%; p: 0.096) and better overall survival (15.1 m vs 11.7 m; p: 0.032) in C1. Thirteen patients (28.9%) showed 2 or more reactivities before treatment; this was associated with worse PFS (5.5 m vs 7.3 m; p: 0.005) in patients treated with chemoimmunotherapy. NAA titers decreased after therapy in 68.9% patients, with no differential patterns of change between cohorts. Patients whose NAA titer decreased after treatment, showed longer OS [18.5 m (95% CI: 15.8 – 21.2)] compared with those whose NAA increased [12.3 m (95% CI: 8.1 – 16.5; p 0.049)], suggesting that antibody levels correlate to tumor load. Our findings reinforce the role of NAAs as prognostic markers and tumor activity/burden in SCLC, warrant further investigation in their predictive role for immunotherapy and raise concern over the use of immunotherapy in patients with more than one anti-NAA reactivity.